Nutrient composition of native vegetation growing in the pastures of central Tunisia - Gasmi-Boubaker A.; Mosquera Losada R.; Kayouli C.; Rigueiro-Rodríguez A.; Najar T. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
A preliminary research was carried out to evaluate, by chemical composition, dry matter digestibility and mineral concentrations, the nutritive value of native vegetation growing in the pastures of central Tunisia. The study examined 12 species (Artemisia herba-alba Asso., Chrozophora tinctoria (L.) A.H.L. Juss, Solanum vigum, Globularia alypum L., Brassica souliei (Batt.), Colestephus myconis L., Thymus hirtus ssp. algeriensis Willd., Marrubium vulgare L.; Pinus halepensis Mill., Plantago lagopus L., Rosmarinus officinalis L. and Pistacia lentiscus L.) collected in the spring (April and May). Crude protein content ranged from 4.74 (Artemisia herba alba Asso.) to 24.66% dry matter (Brassica souliei Batt.). Most of the species had digestibility values above 50%, which is considered adequate for high animal performance on pastures. Mineral concentration showed that levels of Ca were high and over the standard requirements for small ruminant production. Magnesium, zinc, copper and manganese levels could meet the requirements of small ruminants, but phosphorus and iron levels were slightly deficient for some of the species.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)